Hif1α deletion limits tissue regeneration via aberrant B cell accumulation in experimental pancreatitis - Lee, Kyoung Eun (Cell Rep, 2018)
Pancreatitis is an inflammatory disease of the exocrine pancreas and ranks among the most common gastrointestinal disorders. Inflamed tissues frequently experience conditions of insufficient oxygen availability, or hypoxia. Here we demonstrate that hypoxia and consequent stabilization of the hypoxia-inducible factor 1α (HIF1α) transcription factor occur in murine and human pancreatitis. Mice lacking pancreas-specific HIF1α expression displayed markedly impaired pancreatic regeneration following cerulein-induced pancreatitis, which was associated with excessive intrapancreatic B cell accumulation. Notably, B cell depletion in mice with established pancreatitis significantly enhanced tissue regeneration. Our study reveals a crosstalk between pancreatic HIF1α expression and B cell trafficking that regulates tissue regeneration, and identifies plausible molecular targets for treating pancreatitis patients.